Leeuwenhoek's observations on the anatomy of bark - Baas, P. (HOLZFORSCHUNG, 2001)
Leeuwenhoek's letter to the Royal Society of 27 March 1705, dealing with the anatomy of bark of cherry, birch, cinnamon, lime and cork oak is reviewed. It contains many detailed observations and illustrations of, i.a., ray dilatation, various types of phloem sclerenchyma, and annual rings in cork. This is another example of Leeuwenhoek's importance as an early plant anatomist.
The following values have no corresponding Zotero field: pub-location: GENTHINER STRASSE 13, D-10785 BERLIN, GERMANY publisher: WALTER DE GRUYTER & CO
Keywords: biohistory; Cork; fibres; phloem; sclereids